2012
DOI: 10.1152/jn.00541.2011
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal analysis of electrically evoked activity in the chicken optic tectum: a VSDI study

Abstract: Weigel S, Luksch H. Spatiotemporal analysis of electrically evoked activity in the chicken optic tectum: a VSDI study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…The effects of blocking nAChR evoked a disinhibition similar to the effect of GABA A receptor blockade (Weigel & Luksch, ). To conclude whether both results are caused by the same mechanism, we compared the effects of curarine with bicuculline in Fig.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The effects of blocking nAChR evoked a disinhibition similar to the effect of GABA A receptor blockade (Weigel & Luksch, ). To conclude whether both results are caused by the same mechanism, we compared the effects of curarine with bicuculline in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The spatiotemporal activity pattern in the TeO is highly modulated by external input from, for example, the NI that are considered to construct a winner‐takes‐all system by excitatory cholinergic and inhibitory GABAergic feedback (Wang et al ., ). Recently we have shown that the tectal response is controlled by GABAergic inhibition (Weigel & Luksch, ). Here, we tested the influence of cholinergic transmission on the tectal network response by blocking the receptors with the respective antagonists.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations